2019
DOI: 10.3390/ijerph16152806
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Suicides among Victims Who Are under the Influence of Alcohol

Abstract: Introduction: Suicide is one of the most frequent causes of death. According to the World Health Organization (WHO), each year, over eight hundred thousand people worldwide die as a result of suicide. The most common risk factors for suicide are depressive disorders and alcohol dependence. Alcohol can directly influence a decision about suicide, or be a factor facilitating this decision. The aim of the study was to analyse the seasonality of suicides among persons under the influence of alcohol. Material and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…They show that the peak of suicides can be observed in the spring months, although some analyses indicate that the peak can also be observed in autumn [55]. The seasonality phenomenon also applies to suicide attempts [56]. Research conducted by Lasota et al also confirmed the existence of the phenomenon of the seasonality of suicides among victims of suicides under the influence of alcohol.…”
Section: Ethanol Effects On Auto-aggression Behaviourmentioning
confidence: 94%
“…They show that the peak of suicides can be observed in the spring months, although some analyses indicate that the peak can also be observed in autumn [55]. The seasonality phenomenon also applies to suicide attempts [56]. Research conducted by Lasota et al also confirmed the existence of the phenomenon of the seasonality of suicides among victims of suicides under the influence of alcohol.…”
Section: Ethanol Effects On Auto-aggression Behaviourmentioning
confidence: 94%
“…In Poland, the most common method of suicide is hanging, mainly among men, while women most often try to take large amounts of drugs [ 17 , 18 , 19 , 20 , 21 ]. Additionally, in the presented analysis, hanging was the leading method of suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have examined the seasonal variability phenomenon of suicides. The peak for suicides can be observed in the spring months, although some analyses indicate that a peak can also be observed in autumn [ 45 , 46 ]. In the period covered by the RESTRAIL project, the highest number of railway suicides was recorded in April and the lowest in December.…”
Section: Discussionmentioning
confidence: 99%